Contemporary Spirituality and the Thinning of the Sacred: A Hindu Perspective. - Vrajaprana, Pravrajika (Cross Currents)
Examines the 21st century spirituality in the perspective of Hinduism. Hinduism in the spirituality of the West; Sacredness according to the Hindu scriptures; Analysis of the first verse of Isa Upanishad, one of Hinduism's sacred texts; Detachment and renunciation in the Vedanta philosophy.